2015
DOI: 10.1002/hed.24076
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CO2 laser–induced artifact and glottic cancer surgical margins at variable power doses

Abstract: The laser causes less thermal damage at higher power, presumably because of the increased speed of cutting and reduced contact time with surrounding cells. Knowledge of the depth of thermal artifact is important surgically when ensuring the cancer is excised with sufficient oncologic margin. © 2015 Wiley Periodicals, Inc. Head Neck 38: E712-E716, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…This is very likely due to the fact that, in nearly half of our cases, accurate histopathological assessment of surgical margins could not be carried out due to thermal damage of the tissue. This problem in laser surgery has been reported before . Positive tumor margins are a common finding in TLS for laryngeal cancer, because preserving laryngeal function is an important treatment goal besides complete tumor removal .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This is very likely due to the fact that, in nearly half of our cases, accurate histopathological assessment of surgical margins could not be carried out due to thermal damage of the tissue. This problem in laser surgery has been reported before . Positive tumor margins are a common finding in TLS for laryngeal cancer, because preserving laryngeal function is an important treatment goal besides complete tumor removal .…”
Section: Discussionmentioning
confidence: 53%
“…This problem in laser surgery has been reported before. 32 Positive tumor margins are a common finding in TLS for laryngeal cancer, because preserving laryngeal function is an important treatment goal besides complete tumor removal. 33 Small laryngeal cancers can be removed with minimal margins and still be oncologically safe.…”
Section: Surgical Marginsmentioning
confidence: 99%
“…10,11 In a study evaluating the surgical margin after CO 2 laser surgery in T is , T1, and T2 glottic carcinoma, Buchanan et al even observed an inverse relationship between power and thermal tissue damage. 9 Remarkably, none of these studies considered laser duration. Buchanan et al proposed that this inverse correlation could be an indirect effect; using laser irradiation at higher power intensities led to an increase in cutting speed and therefore shorter procedural time, thereby leading to less thermal damage.…”
Section: Discussionmentioning
confidence: 99%
“…2 Few studies were published investigating thermal effects of CO 2 lasers, either using a fiber [5][6][7] or an articulated arm delivery system. 3,[8][9][10][11][12][13] However, none of these studies performed a systematic and complete analysis of the effects of individual CO 2 laser settings. Hence, the exact effect of adjusting laser settings on thermal energy produced by the laser, the depth of laser incision, and the thermal damage to surrounding tissue remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Buchanan et al 29 pointed out that the CO 2 laser induces a thermal cytologic damage that could result in misinterpretation or difficult assessment of margin status. In particular, they report that the CO 2 laser at a higher power causes less tissue damage thanks to the greater speed of the beam and, consequently, reduced contact between it and the cell.…”
Section: Challenges In the Histological Assessment Of Resection Marginsmentioning
confidence: 99%